Paramagnetic garnet-type transparent ceramics and magneto-optical device

JP2025003006AActive Publication Date: 2025-01-09SHIN ETSU CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023103433
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09
Estimated Expiration
2043-06-23

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、Scを実質的に含まなくても、光路長20mmでの波長1,064nmにおける反射を除いた光の挿入損失が0.05dB以下であり、光路長20mmにおける波長1,070nmのレーザー光をビーム径1.6mm、入射パワー100Wで入射した場合のビーム径変化率が15%以下である熱レンズ効果の小さい常磁性ガーネット型透明セラミックスを提供でき、光アイソレータなどの磁気光学デバイスを構成するのに好適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003006000001_ABST
    Figure 2025003006000001_ABST
Patent Text Reader

Abstract

To provide a novel paramagnetic garnet-type transparent ceramic that does not intentionally contain Sc and can replace TYSAG, and to provide a magneto-optical device using the same.SOLUTION: A paramagnetic garnet-type transparent ceramics that includes a sintered body containing 99 mass% or more of a complex oxide represented by the following formula (1): Tb8-x-y-zYxLuyAlzO12 (1) (where 0.10≤x<1.35, 0.05≤y<0.30, 4.80≤z≤5.00, 5.00≤y + z.) Insertion loss of light, excluding reflection at a wavelength of 1,064 nm at an optical path length of 20 mm, is less than 0.05 dB. The magneto-optical element is an optical isolator that has the paramagnetic garnet-type transparent ceramics as a Faraday rotator 110, and a polarizer 120 and an analyzer 130 in front of and behind the optical axis 104 of the Faraday rotator, and can be used in the wavelength range of 0.9-1.1 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a paramagnetic garnet-type transparent ceramic having transparency in the visible and / or near-infrared region and a magneto-optical device, and more particularly to a terbium-containing paramagnetic garnet-type transparent ceramic suitable for constituting a magneto-optical device such as an optical isolator, and a magneto-optical device using the same. [Background technology]

[0002] Industrial laser processing machines are equipped with optical isolators to prevent the return of light, such as reflected light, and inside these machines terbium-doped glass or terbium gallium garnet (TGG) is installed as a Faraday rotator (for example, JP 2011-213552 A (Patent Document 1)). The magnitude of the Faraday effect is quantified by the Verdet constant, and the Verdet constant of TGG crystal is 40 rad / (T·m) (0.13 min / (Oe·cm)), while that of terbium-doped glass is 0.098 min / (Oe·cm). Since the Verdet constant of TGG crystal is relatively large, it is widely used as a standard Faraday rotator. Other garnets containing aluminum include terbium scandium aluminum garnet crystals (TSAG crystals), terbium scandium lutetium aluminum garnet crystals (TSLAG crystals) (for example, JP 2017-137223 A (Patent Document 2)), and terbium aluminum garnet crystals (TAG crystals). In particular, the Verdet constant of TAG crystals is about 1.3 times that of TGG crystals, which allows the length of the Faraday rotator to be shortened, making them suitable crystals that can be used in fiber lasers (for example, JP 2002-293693 A (Patent Document 3), WO 2004 / 029339 (Patent Document 4)).

[0003] In recent years, methods for producing TAG from transparent ceramics have been disclosed (for example, International Publication No. WO 2017 / 033618 (Patent Document 5), International Publication No. WO 2018 / 193848 (Patent Document 6), International Publication No. WO 2022 / 054596 (Patent Document 7), and “High Verdet constant of Ti-doped terbium aluminum garnet (TAG) ceramics” (Non-Patent Document 1)). In addition, YTAG (Tb x Y 1-x )3AlO 12 Methods for fabricating transparent ceramics with x=0.2≦x≦0.8, 0.5≦x≦1.0, or x=0.6 have also been reported (see, for example, “Fabrication and properties of (Tb x Y 1-x )3AlO 12 "Transparent ceramics by hot isostatic pressing" (Non-Patent Document 2), "Development of optical grade (Tb x Y 1-x )3AlO 12 "Effect of (Tb+Y) / Al ratio on Microstructure Evolution and Densification Process of (Tb 0.6 Y 0.4 )3AlO 12 Rare earth aluminum garnet containing Tb exhibits higher thermal conductivity than TGG, and is therefore expected to become a Faraday element with a smaller thermal lens effect. Furthermore, an optical isolator equipped with trivalent ion-substituted TAG transparent ceramics has been disclosed, and it has been shown to have a smaller thermal lens effect than an optical isolator equipped with TGG (for example, JP 2020-067523 A (Patent Document 8)). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2011-213552 [Patent Document 2] Japanese Patent Publication No. 2017-137223 [Patent Document 3] Japanese Patent Publication No. 2002-293693 [Patent Document 4] International Publication No. 2004 / 029339 [Patent Document 5] International Publication No. 2017 / 033618 [Patent Document 6] International Publication No. 2018 / 193848 [Patent Document 7] International Publication No. 2022 / 054596 [Patent Document 8] JP-2020-067523

Non-licensed documents

[0005]

Non-patent document 1

Non-patent document 2

Non-patent document 3

[0006] Terbium yttrium scandium aluminum garnet (TYSAG)-based transparent ceramics for Faraday rotators have been invented, and optical isolators equipped with them have been put on the market (Patent Document 7, Patent Document 8). The material disclosed in Patent Document 7 is an essential element for stabilizing production, since the generation of phases other than the garnet phase is suppressed by adding a small amount of Sc. This effect is thought to be due to the fact that Sc can enter the 8-coordinated site and the 6-coordinated site of the garnet crystal structure, and therefore acts to buffer deviations from the garnet composition ratio at the time of weighing the raw materials. Therefore, Sc has been regarded as a so-called auxiliary agent that does not affect the material properties of the base material in rare earth aluminum garnet, but it has been suggested that it may have a small amount of absorption in the near infrared region (either directly or indirectly due to impurities). In addition, Sc is generally expensive, and it is difficult to obtain high-purity raw materials, so reducing its usage has been an issue.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a new paramagnetic garnet-type transparent ceramic material which does not intentionally contain Sc and which can replace TYSAG, and a magneto-optical device using the same. [Means for solving the problem]

[0008] As a result of investigations into the above-mentioned problems, the inventors have found that by adding Lu(III) ions, which have an intermediate ion diameter that is smaller than that of Tb(III) ions and Y(III) ions but larger than that of Al(III) ions, are a trivalent cation that can be a constituent element of rare earth aluminum garnet, and are an element that does not absorb in the near infrared region, it is possible to produce transparent ceramics that have the same Verdet constant, insertion loss, and thermal lens effect as TYSAG.Based on this finding, the inventors have conducted extensive investigations and have completed the present invention.

[0009] As one aspect thereof, the present invention provides a paramagnetic garnet-type transparent ceramic, comprising a sintered body containing 99 mass percent or more of a composite oxide represented by the following formula (1): Tb 8-x-y-z Y x Lu y Al z O 12 (1) (In the formula, 0.10≦x<1.35, 0.05≦y<0.30, 4.80≦z<5.00, and 5.00≦y+z.) The insertion loss of light excluding reflection at a wavelength of 1,064 nm with an optical path length of 20 mm is 0.05 dB or less.

[0010] The paramagnetic garnet-type transparent ceramics according to the present invention may contain more than 0.00 mass % and 0.10 mass % or less of SiO2 as a sintering aid.

[0011] The paramagnetic garnet-type transparent ceramic according to the present invention preferably has a Verdet constant of 30 rad / (T·m) or more at a wavelength of 1,064 nm.

[0012] In the paramagnetic garnet-type transparent ceramics according to the present invention, it is preferable that the absolute value of the rate of change in beam diameter due to thermal lensing is 15% or less when laser light with a wavelength of 1,070 nm and an optical path length of 20 mm is incident with a beam diameter of 1.6 mm and an incident power of 100 W.

[0013] Another aspect of the present invention is a magneto-optical device that is constructed using the above-mentioned paramagnetic garnet-type transparent ceramics.

[0014] The magneto-optical device according to the present invention is preferably an optical isolator that has the above-mentioned paramagnetic garnet-type transparent ceramics as a Faraday rotator and has polarizing materials in front of and behind the optical axis of the Faraday rotator and can be used in the wavelength range of 0.9 μm or more and 1.1 μm or less. Effect of the Invention

[0015] According to the present invention, it is possible to provide a paramagnetic garnet-type transparent ceramic having a small thermal lens effect, even if it is substantially free of Sc, in which the insertion loss of light excluding reflection at a wavelength of 1,064 nm over an optical path length of 20 mm is 0.05 dB or less, and the beam diameter change rate when laser light having a wavelength of 1,070 nm over an optical path length of 20 mm is incident with a beam diameter of 1.6 mm and an incident power of 100 W, is 15% or less, and the ceramic is suitable for forming magneto-optical devices such as optical isolators. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic cross-sectional view showing an example of the configuration of an optical isolator using the paramagnetic garnet-type transparent ceramic according to the present invention as a Faraday rotator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] [1. Paramagnetic garnet-type transparent ceramics] The paramagnetic garnet-type transparent ceramic according to the present invention will be described below. The paramagnetic garnet-type transparent ceramic according to the present embodiment includes a sintered body containing 99 mass percent or more of a composite oxide represented by the following formula (1): Tb 8-x-y-z Y x Lu y Al z O 12 (1) (In the formula, 0.10≦x<1.35, 0.05≦y<0.30, 4.80≦z<5.00, and 5.00≦y+z.) The insertion loss of light excluding reflection at a wavelength of 1,064 nm over an optical path length of 20 mm is 0.05 dB or less.

[0018] In general, the garnet composition formula is A3B2C3O, which shows the difference in the coordination structure of the metal ions. 12 In the rare earth aluminum garnet crystal structure, the 8-coordinated sites mainly occupied by rare earth ions such as Tb are called A sites, and the 6-coordinated sites and 4-coordinated sites mainly occupied by Al ions are called B sites and C sites, respectively.

[0019] In the A site of the above composition formula, terbium (Tb) is an element with the largest Verdet constant among trivalent rare earth ions, and has extremely small absorption in the 1,070 nm region (wavelength band 0.9 μm or more and 1.1 μm or less) used in fiber lasers, making it the most suitable element for use as a material for optical isolators in this wavelength range. However, Tb(III) ions are easily oxidized to generate Tb(IV) ions. When Tb(IV) ions are generated in metal oxides, they absorb light over a wide range of wavelengths from ultraviolet to near infrared, reducing transmittance, so it is desirable to eliminate them as much as possible. One strategy to prevent the generation of Tb(IV) ions is to adopt a crystal structure in which Tb(IV) ions are unstable, i.e., a garnet structure.

[0020] Yttrium (Y) has an ionic radius that is approximately 2% smaller than that of terbium, and when combined with aluminum to form a composite oxide, it can form a garnet phase more stably than a perovskite phase, and is therefore an element that can be preferably used in the present invention.

[0021] In the B site of the above composition formula, aluminum (Al) is a material having the smallest ionic radius among trivalent ions that can stably exist in an oxide having a garnet structure, and is an element that can minimize the lattice constant of a paramagnetic garnet-type oxide containing Tb. If the lattice constant of the garnet structure can be reduced without changing the content of Tb, it is preferable because the Verdet constant per unit length can be increased. Furthermore, since aluminum is a light metal, it has weak diamagnetism compared to gallium, and is expected to have the effect of relatively increasing the magnetic flux density generated inside the Faraday rotator, which is also preferable because it can increase the Verdet constant per unit length. In fact, the Verdet constant of TAG ceramics is improved to 1.25 to 1.5 times that of TGG. Therefore, even if the relative concentration of terbium is reduced by replacing some of the terbium ions with yttrium ions, it is possible to keep the Verdet constant per unit length equal to or slightly lower than that of TGG, so it is a suitable constituent element in the present invention.

[0022] Here, a composite oxide whose constituent elements are only Tb, Y and Al may not have a garnet structure due to a subtle weighing error, and it is difficult to stably manufacture transparent ceramics that can be used for optical applications. Therefore, in the present invention, lutetium (Lu) is added as a constituent element to eliminate the composition deviation due to a subtle weighing error. Lu is a material with an intermediate ionic radius that can be dissolved in both the A site and the B site in an oxide having a garnet structure, and is a buffer material that can adjust the distribution ratio to the A site (rare earth site consisting of Tb and Y) and the B site (aluminum site) to exactly match the stoichiometric ratio and thereby minimize the energy of crystallite formation when the compounding ratio of rare earth elements consisting of Tb and Y and Al deviates from the stoichiometric ratio due to variations in weighing. In addition, it is an element that can limit the presence ratio of the alumina heterophase in the garnet parent phase to 1 ppm or less, and the presence ratio of the perovskite-type heterophase in the garnet parent phase to 1 ppm or less, and is an element that can be added to improve product yields.

[0023] In formula (1), the range of x is 0.10≦x<1.35, preferably 0.50≦x<1.35, and more preferably 1.00≦x≦1.30. When x is in this range, the Verdet constant at room temperature (23±15℃) and wavelength of 1,064 nm is 30 rad / (T·m) or more, and it can be used as a Faraday rotator. In addition, the larger x is in this range, the smaller the thermal lens effect tends to be, which is preferable. Furthermore, in this range, the larger x is, the smaller the insertion loss per unit length tends to be, which is preferable. The same applies to laser light with a wavelength of 1,070 nm. On the other hand, when x is 1.35 or more, the Verdet constant at a wavelength of 1,064 nm is less than 30 rad / (T·m), which is not preferable. In other words, if the relative concentration of Tb is excessively low, when a typical magnet is used, the total length of the Faraday rotator required to rotate laser light with a wavelength of 1,064 nm (or 1,070 nm) by 45 degrees will exceed 30 mm, making manufacturing difficult, which is undesirable.

[0024] In formula (1), the range of y is 0.05≦y<0.30, and preferably 0.10≦y≦0.25. When y is in this range, the perovskite type heterophase can be reduced to a level that is not detected by X-ray diffraction (XRD) analysis. Furthermore, it is preferable because the number of perovskite type heterophases (typically 1 to 1.5 μm in diameter and granular, light brown colored particles) in a field of view of 150 μm×150 μm observed by an optical microscope is one or less. In this case, the ratio of the perovskite type heterophase to the garnet matrix is ​​1 ppm or less. On the other hand, when y is 0.30 or more, in addition to substituting a part of Tb with Y, further substituting a part of Tb with Lu, which results in an unnecessary decrease in the solid solution concentration of Tb, which is undesirable because the Verdet constant becomes small.

[0025] In formula (1), the range of z is 4.80≦z<5.00, preferably 4.85≦z≦4.98, and more preferably 4.90≦z≦4.98. When z is in this range, the perovskite-type heterophase is not detected by XRD analysis. Furthermore, it is preferable because the number of perovskite-type heterophases (typically 1 to 1.5 μm in diameter and granular, light brown in color) present in a 150 μm×150 μm field of view is one or less in optical microscope observation. In this case, the ratio of the perovskite-type heterophase to the garnet mother phase is 1 ppm or less.

[0026] In formula (1), the range of y+z is 5.00≦y+z. When y+z is in this range, the perovskite-type heterogeneous phase is not detected by XRD analysis. Furthermore, when observed by optical microscope, the number of perovskite-type heterogeneous phases (typically 1 to 1.5 μm in diameter and granular, light brown in color) present in a field of view of 150 μm × 150 μm is preferably 1 or less. In this case, the ratio of the perovskite-type heterogeneous phase to the garnet parent phase is 1 ppm or less.

[0027] In the paramagnetic garnet-type transparent ceramics of this embodiment, it is preferable that Sc is not added to the sintered body. Specifically, the content of Sc2O3 relative to the total mass of the paramagnetic garnet-type transparent ceramics is preferably 0.5 mass% or less (5,000 ppm or less), more preferably 0.3 mass% or less (3,000 ppm or less), and even more preferably 0.1 mass% or less (1,000 ppm or less). If the content exceeds 0.5 mass% (5,000 ppm), a slight amount of light absorption may occur.

[0028] In addition, in the paramagnetic garnet-type transparent ceramic of the present embodiment, the sintered body preferably further contains a sintering aid. Specifically, it is preferable that the sintering aid contains SiO2 in an amount of more than 0 mass% and 0.1 mass% or less (more than 0 ppm and 1,000 ppm or less). If the content exceeds 0.1 mass% (1,000 ppm), a slight amount of light absorption may occur due to crystal defects caused by the excessive Si contained, and when a manufactured paramagnetic garnet-type transparent ceramic having a length (optical path length) of 20 mm is irradiated with a 100 W laser beam having a wavelength of 1,070 nm, a thermal lens effect occurs, so that when a laser beam having a wavelength of 1,070 nm is incident with a beam diameter of 1.6 mm and an incident power of 100 W at an optical path length of 20 mm, the beam diameter change rate becomes larger than 15%, which is not preferable.

[0029] In addition, an oxide of magnesium (Mg) or calcium (Ca) can be added as a sintering aid. Both Mg and Ca are divalent ions, and can compensate for the charge balance deviation in the garnet structure caused by the addition of SiO2, which is tetravalent, so they can be suitably added. The amount of addition is preferably adjusted to match the amount of SiO2 added.

[0030] The paramagnetic garnet-type transparent ceramic of this embodiment has an insertion loss of 0.05 dB or less for light at a wavelength of 1,064 nm, excluding reflection, over an optical path length of 20 mm. This means that the paramagnetic garnet-type transparent ceramic is a cylindrical or polygonal prism 20 mm in length, with both end faces optically mirror-finished and then each end face formed with an anti-reflection film, and the insertion loss for light at a wavelength of 1,064 nm is 0.05 dB or less.

[0031] Furthermore, the paramagnetic garnet-type transparent ceramics of this embodiment preferably have a Verdet constant of 30 rad / (T m) or more at a wavelength of 1,064 nm. The upper limit of the Verdet constant is not particularly limited, but may be, for example, 60 rad / (T m) or less.

[0032] In addition, the paramagnetic garnet-type transparent ceramic of this embodiment preferably has a beam diameter change rate due to thermal lensing of 15% or less when a laser beam having a wavelength of 1,070 nm is incident with a beam diameter of 1.6 mm and an incident power of 100 W at an optical path length of 20 mm, more preferably 10% or less, even more preferably 9% or less, and even more preferably 8% or less. If the beam diameter change rate due to the thermal lens effect is 10% or less at a certain incident power, the system can be installed at that incident power, that is, the thermal lens characteristics pass. Some of the paramagnetic garnet-type transparent ceramics of this embodiment, especially those with a high content of terbium ions, show a beam diameter change rate of more than 10% at an optical path length of 20 mm, but when used as a Faraday rotator, the length is shorter than 20 mm, so when processed into a Faraday rotator length, the beam diameter change rate due to the thermal lens effect can be controlled to 10% or less at a high power incident of 100 W, and therefore the material can be practically adopted in a high-power laser system for 100 W. The lower limit of the rate of change of the beam diameter under the above conditions is not particularly limited, but may be, for example, 0.1% or more.

[0033] [2. Manufacturing method of paramagnetic garnet-type transparent ceramics] Next, an embodiment of a method for producing a paramagnetic garnet-type transparent ceramic according to the present invention will be described. The manufacturing method of this embodiment includes the steps of preparing a raw powder for sintering, forming a slurry containing the raw powder for sintering into a predetermined shape to obtain a molded body, degreasing the molded body to obtain a degreased body, pre-sintering the degreased body to obtain a sintered body (pre-sintered body) made of a complex oxide densified to a relative density of 94% or more, then pressure-sintering the pre-sintered body to obtain a pressure-sintered body, further heating the pressure-sintered body to a temperature higher than the pressure-sintering temperature to re-sinter the pressure-sintered body to obtain a re-sintered body, and performing an oxidation annealing treatment on the re-sintered body. Each step will be described below.

[0034] [2-1. Preparation process of raw powder for sintering] A raw powder for sintering corresponding to the composition of the complex oxide represented by the above formula (1) is prepared.

[0035] The process for preparing the raw powder for sintering is not particularly limited, but may be such that the metal oxide powders of each of the elements terbium, yttrium, lutetium, and aluminum are used as starting materials, and a predetermined amount of each is weighed out so as to obtain a composition corresponding to formula (1), and then mixed to obtain the raw powder for sintering. The starting material at this time is not particularly limited as long as it can be made transparent, but from the viewpoint of suppressing absorption derived from impurities, the purity is preferably 99.9 mass% or more, more preferably 99.99 mass% or more, and most preferably 99.999 mass% or more. In addition, the particle size of the primary particles of the raw powder is not particularly limited as long as it can be made transparent, but from the viewpoint of easy sintering, it is preferably 50 nm or more and 1,000 nm or less. The shape of the primary particles is selected from a card house shape, a spherical shape, and a rod shape, and is not particularly limited as long as it can be made transparent.

[0036] Alternatively, the process for preparing the raw powder for sintering may be a coprecipitation method, a pulverization method, a spray pyrolysis method, a sol-gel method, an alkoxide hydrolysis method, a complex polymerization method, a homogeneous precipitation method, or any other synthesis method. In some cases, the obtained ceramic raw material of rare earth composite oxide may be appropriately processed by a wet ball mill, a bead mill, a jet mill, a dry jet mill, a hammer mill, or the like to obtain a desired particle size. For example, the raw powder for sintering may be prepared by a solid-phase reaction method in which a plurality of oxide particles are mixed and fired to produce uniformity by thermal diffusion of ions, or a coprecipitation method in which hydroxides, carbonates, etc. are precipitated from an ion-containing solution in which oxide particles are dissolved, and then fired to produce oxides to produce uniformity.

[0037] In the case of the solid-phase reaction method in which a plurality of metal oxide particles are mixed and fired to produce uniformity by thermal diffusion of ions, the starting materials can be preferably terbium, yttrium, lutetium, or aluminum metal powders, or the above metal powders dissolved in an aqueous solution of nitric acid, sulfuric acid, uric acid, or the like, or oxide powders of the above elements. The purity of the above raw materials is preferably 99.9% by mass or more, and particularly preferably 99.99% by mass or more. The starting materials can be weighed in a predetermined amount so as to have a composition corresponding to formula (1), mixed, and then fired to obtain a fired raw material of the desired metal oxide, which can then be crushed to obtain a raw material powder for sintering. However, the firing temperature at this time is preferably 1,100°C or less, more preferably 1,050°C or less, and even more preferably 1,000°C or less. If the firing temperature exceeds 1,100°C, the raw material powder will be sintered and may not be sufficiently crushed in the subsequent crushing process. The firing time may be 1 hour or more, and the heating rate is preferably 100° C. / h or more and 500° C. / h or less. The firing atmosphere is preferably air or an oxygen-containing atmosphere, and nitrogen atmosphere, argon atmosphere, hydrogen atmosphere, etc. are not suitable. The firing apparatus is not particularly limited as long as it can reach the target temperature and oxygen flow is possible, and examples of the firing apparatus include a vertical muffle furnace, a horizontal tubular furnace, and a rotary kiln.

[0038] In addition, the raw powder for sintering preferably contains a sintering aid. For example, tetraethoxysilane (TEOS) is added as a sintering aid together with the above starting materials in an amount of more than 0 ppm and less than 1,000 ppm (more than 0 mass% and less than 0.1 mass%) in terms of SiO2 in the entire raw powder (complex oxide + sintering aid), or SiO2 powder is added in an amount of more than 0 ppm and less than 1,000 ppm (more than 0 mass% and less than 0.1 mass%) in the entire raw powder (complex oxide + sintering aid), mixed, and formed as necessary to obtain raw powder for sintering. If the amount added exceeds 1,000 ppm, there is a risk of slight light absorption occurring due to crystal defects caused by the excessive Si contained. The purity is preferably 99.9 mass% or more. The sintering aid may be added when preparing the raw powder slurry. Note that Si element may be mixed in from the environment, such as glassware used in the manufacturing process, or may volatilize when sintering is performed under reduced pressure, so care must be taken because the Si content in the final ceramic may increase or decrease unintentionally when analyzed. In addition, when no sintering aid is added, it is advisable to select the raw material powder for sintering (i.e., the above-mentioned starting material mixed powder or composite oxide powder) to be used, whose primary particles have a nano-sized particle size and have extremely high sintering activity. Such a selection may be made as appropriate.

[0039] When the firing raw material is pulverized to obtain the sintering raw material powder, either a dry or wet pulverization method can be selected, but it is necessary to pulverize so that the target ceramics become highly transparent. For example, in the case of wet pulverization, the firing raw material is slurried by various pulverization (dispersion) methods such as a ball mill, a bead mill, a homogenizer, a jet mill, and ultrasonic irradiation, and then pulverized (dispersed) to primary particles. The dispersion medium of this wet slurry is not particularly limited as long as it can make the final ceramic highly transparent, and examples of the dispersion medium include alcohols such as lower alcohols having 1 to 4 carbon atoms and pure water. In addition, various organic additives may be added to this wet slurry for the purpose of improving the quality stability and yield in the subsequent ceramic manufacturing process. In the present invention, these are also not particularly limited. That is, various dispersants, binders, lubricants, plasticizers, etc. can be suitably used. However, it is preferable to select high-purity types of organic additives that do not contain unnecessary metal ions. In the case of wet pulverization, the dispersion medium of the slurry is finally removed to obtain the sintering raw material powder.

[0040] [2-2. Molding process] The slurry thus obtained is subjected to solid-liquid separation and molded into a desired shape. The molding method is broadly divided into dry molding and wet molding, but is not particularly limited as long as the desired shape can be stably obtained. In the case of dry molding, a method of making granules from the slurry using spray drying, filling a jig with the granules, and then performing press molding is exemplified. In addition, an example of wet molding is a casting molding method in which the slurry is poured into a plaster mold and the solvent is volatilized. Other examples include extrusion molding, sheet molding, centrifugal casting molding, and cold isostatic pressing, but all of these methods are not limited as they can obtain a desired shape.

[0041] Before molding, a binder may be added to the slurry. The binder can increase the holding power of the molded body and has the effect of making cracks and breaks less likely to occur. The type of binder is not particularly limited, but it is preferable that it is compatible with the solvent and does not leave a residue after heat treatment. Examples of the binder include polyvinyl alcohol, polyvinyl butyral, polyvinyl acetate, and polyacrylic acid, and a polymer obtained by copolymerizing two or more of these may be used. The amount of binder varies depending on the molding method or binder type, but a minimum of 0.5% by mass is required with respect to the raw powder for sintering, and the upper limit is 8% by mass. It is most preferable to add the binder during wet grinding.

[0042] As the press molding, a normal press molding process can be suitably used. That is, a very common uniaxial pressing process in which the material is filled into a mold and pressed from a certain direction, a cold isostatic pressing (CIP) process in which the material is sealed in a deformable waterproof container and pressed with hydrostatic pressure, or a warm isostatic pressing (WIP) process can be suitably used. The applied pressure can be appropriately adjusted while checking the relative density of the resulting molded body, and is not particularly limited. For example, the manufacturing cost can be reduced by controlling the pressure within a pressure range of about 300 MPa or less that can be handled by a commercially available CIP device or WIP device.

[0043] However, in the present invention, in order to control the size and amount of scattering sources such as foreign phases, foreign bodies, dirt, and microcracks within specified ranges, it is preferable that the molding jigs and molding machines used are clean and dedicated ones that have been thoroughly washed and dried, and that the environment in which the molding work is carried out is a clean space of class 1000 or less.

[0044] [2-3. Degreasing] In the manufacturing method of this embodiment, a normal degreasing process can be suitably used. That is, a temperature-raising degreasing process using a heating furnace can be used. In addition, the type of atmospheric gas used at this time is not particularly limited, and air, oxygen, hydrogen, etc. can be suitably used. There is also no particular limit to the degreasing temperature, but if a raw material containing an organic additive is used, it is preferable to raise the temperature to a temperature at which the organic component can be decomposed and eliminated.

[0045] [2-4. Pre-sintering process] In this process, a pre-sintered body is prepared as a sintered body before heat sintering, which is preferably densified to a relative density of 94% or more and preferably has an average sintered grain size of 5 μm or less. At this time, it is necessary to determine the temperature and holding time conditions so that the sintered grain size falls within the desired range.

[0046] In the manufacturing method of this embodiment, a general sintering process can be preferably used. That is, a heat sintering process such as a resistance heating method or an induction heating method can be preferably used. The atmosphere at this time is not particularly limited, and various atmospheres such as air, inert gas, oxygen gas, hydrogen gas, and helium gas can be preferably used, but sintering under reduced pressure (in a vacuum) is more preferably used. The degree of vacuum for pre-sintering is 1×10 -1 Pa or less is preferable, and 1×10 -2 Pa or less is more preferable, and 1×10 -3 Less than Pa is particularly preferred.

[0047] The sintering temperature in the pre-sintering step of this embodiment is preferably 1,450 to 1,650°C, and particularly preferably 1,500 to 1,600°C. This range of sintering temperature is preferable because it promotes densification while suppressing heterophase precipitation and grain growth. Although the sintering holding time in the pre-sintering step of this embodiment is sufficient for several hours, it is preferable to densify the pre-sintered body to a relative density of 94% or more. If the relative density of the pre-sintered body is higher than 99%, it becomes difficult for the internal particles of the sintered body to undergo plastic deformation in the subsequent hot-press sintering (HIP), and it becomes difficult to remove the bubbles remaining in the sintered body. Therefore, the relative density of the pre-sintered body is preferably 99% or less at most, and more preferably 98% or less.

[0048] The average sintered grain size of the pre-sintered body in this embodiment is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 2.5 μm or less, and particularly preferably 1 μm or less. The average sintered grain size of the sintered grains can be adjusted depending on the raw material type, atmosphere, sintering temperature, and holding time. If the sintered grain size is larger than 5 μm, plastic deformation is unlikely to occur in the subsequent hot-ip sintering (HIP), and it may be difficult to remove bubbles remaining in the pre-sintered body. The average sintered grain size of the pre-sintered body can be determined by observing the sintered grain size of the crystal grains on the surface of the transparent hot-ip sintered body obtained in the next process with an optical microscope.

[0049] [2-5. Pressure sintering (hot isostatic pressing (HIP))] In the manufacturing method of this embodiment, after the pre-sintering step, the pre-sintered body is subjected to a step of pressure sintering (HIP treatment) preferably at a pressure of 50 MPa or more and 300 MPa or less and at a temperature of 1,000°C or more and 1,780°C or less. In addition, the type of the pressurized gas medium at this time is preferably an inert gas such as argon or nitrogen, or Ar-O2. The pressure applied by the pressurized gas medium is preferably 50 to 300 MPa, more preferably 100 to 300 MPa. If the pressure is less than 50 MPa, the transparency improvement effect may not be obtained, and if the pressure exceeds 300 MPa, even if the pressure is increased, no further transparency improvement is obtained, and the load on the device may become excessive, which may damage the device. The applied pressure is preferably 196 MPa or less, which can be processed by a commercially available HIP device, for convenience. In addition, the processing temperature (predetermined holding temperature) at this time is preferably set in the range of 1,000 to 1,780°C, more preferably 1,100 to 1,700°C. Heat treatment temperatures higher than 1,780°C are not preferred because they cause grain growth during HIP treatment, making it difficult to remove bubbles. Heat treatment temperatures lower than 1,000°C may not provide much transparency improvement to the sintered body. There is no particular restriction on the time the heat treatment temperature is held, but holding it for too long increases the risk of oxygen deficiency, which is not preferred. Typically, the time is set within the range of 1 to 3 hours.

[0050] The heater material, heat insulating material, and processing vessel for HIP processing are not particularly limited, but graphite (C), molybdenum (Mo), tungsten (W), and platinum (Pt) can be preferably used, and yttrium oxide and gadolinium oxide can also be preferably used as the processing vessel. When the processing temperature is 1,500°C or higher, graphite is preferable as the heater material and heat insulating material, but in this case, it is preferable to select graphite, molybdenum, or tungsten as the processing vessel, and further select yttrium oxide or gadolinium oxide as a double vessel inside it, and fill the vessel with an oxygen release material, since this minimizes the amount of oxygen deficiency during HIP processing.

[0051] [2-6. Re-sintering process] In the manufacturing method of this embodiment, after the HIP process, the pressure-sintered compact is heated to a temperature higher than that of the pressure-sintering process, and re-sintered to grow grains and obtain a re-sintered compact. At this time, it is necessary to determine the temperature and holding time conditions so that the final sintered grain size falls within the desired range.

[0052] The type of atmospheric gas used here is not particularly limited, and air, oxygen, hydrogen, etc. can be suitably used. -3 It is more preferable to treat the powder at a vacuum of less than 1 Pa. The resintering temperature is preferably 1,650° C. or higher and 1,800° C. or lower, and more preferably 1,700° C. or higher and 1,800° C. or lower. Temperatures below 1,650° C. are not preferable because grain growth does not occur.

[0053] The average sintered grain size of the crystal grains by resintering is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. It is also preferably 40 μm or less. The holding time of the resintering process is not particularly limited, but is preferably 5 hours or more, more preferably 10 hours or more, and particularly preferably 20 hours or more. In general, the longer the holding time, the more the grain growth of the sintered body progresses. The temperature and holding time of the resintering process may be appropriately adjusted after checking the average sintered grain size. However, generally, if the sintering temperature is raised too much, unexpected abnormal grain growth occurs, making it difficult to obtain a homogeneous sintered body. Therefore, it is preferable to allow a certain amount of leeway in the resintering temperature, and to adjust the size of the average sintered grain size of the resintered body by extending the holding time.

[0054] [2-7. Oxidation annealing process] The resintered body that has undergone the above series of treatments may have some oxygen deficiency due to reduction, particularly in the HIP treatment process, and may have a gray to dark blue appearance. Therefore, an oxidation annealing treatment (oxygen deficiency recovery treatment) is performed in an oxidizing atmosphere (oxygen-containing atmosphere) such as air. The annealing temperature is 1,400°C or higher, preferably 1,450°C or higher. It is also preferable that it is 1,500°C or lower. In this case, the holding time is not particularly limited, but it is preferable to select a time that is sufficient to recover the oxygen deficiency and is within a time that does not consume electricity by performing the treatment for a long time unnecessarily. In addition, a slight oxidation HIP treatment may be performed. By these treatments, even if the resintered body has become colored, the oxygen deficiency can be restored, so that the size and number of the scattering source (scattering contrast source) can be controlled within a specified range, and a paramagnetic garnet-type transparent ceramic with little absorption due to oxygen deficiency can be obtained. Of course, the intrinsic coloring (absorption) of the material caused by the addition of colored elements such as dopants and impurities for imparting functions cannot be removed.

[0055] In addition, if the oxidation annealing process is performed at too high a temperature for too long a period of time, the size and amount of bubbles remaining inside the sintered body may increase. This is not preferable because it makes it impossible to control the size and amount of bubbles and microcracks remaining inside the final sintered body within a specified range. In this case, it is preferable to perform HIP treatment on the sintered body again and then perform annealing treatment in an oxygen atmosphere again, since this makes it possible to control the size and amount of bubbles and microcracks remaining inside the sintered body within a specified range.

[0056] In the method for producing the paramagnetic garnet-type transparent ceramic of this embodiment, after the above-mentioned oxidation annealing treatment, it is preferable that both end faces are finished to an optical mirror surface, and then an anti-reflection film is formed on each of the end faces.

[0057] [2-8. Optical polishing] In the manufacturing method of this embodiment, the paramagnetic garnet-type transparent ceramics that have undergone the above-mentioned series of manufacturing steps preferably have a cylindrical or polygonal columnar shape, and both end faces (optical end faces) on the optically utilized axis are preferably optically polished and finished (optically mirror finished). In this case, the optical surface precision is preferably λ / 2 or less, particularly preferably λ / 8 or less, when the measurement wavelength λ=633 nm.

[0058] It is also possible to further reduce optical loss by forming an appropriate anti-reflection film (AR coating) on ​​the optically polished surface. In this case, it is preferable to thoroughly clean the optical surface with a chemical solution and inspect the cleanliness with a stereoscope or microscope before applying the anti-reflection coating so that no dirt remains on both optical end faces. If the inspection determines that the cleanliness is low, it can be wiped clean. In order not to scratch the optical surface or rub dirt on it during the wipe-cleaning process, it is preferable to select a handling jig made of a soft material and a wiping tool that generates little dust.

[0059] In this manner, it is possible to obtain a paramagnetic garnet-type transparent ceramic that contains a sintered body containing 99% by mass or more of the terbium-yttrium-lutetium-aluminum composite oxide represented by formula (1) and has an insertion loss of 0.05 dB or less for light at a wavelength of 1,064 nm, excluding reflection, over an optical path length of 20 mm.

[0060] [3. Magneto-optical devices] Further, an embodiment of the magneto-optical device according to the present invention will be described. The above-mentioned terbium-containing paramagnetic garnet-type transparent ceramics are intended to be used as magneto-optical materials, and the magneto-optical device of this embodiment is constructed using the above-mentioned paramagnetic garnet-type transparent ceramics. Specifically, it is preferable to apply a magnetic field parallel to the optical axis of the above-mentioned terbium-containing paramagnetic garnet-type transparent ceramics, and then set a polarizer and an analyzer so that their optical axes are shifted by 45 degrees from each other to construct and use the magneto-optical device. In particular, the above-mentioned paramagnetic garnet-type transparent ceramics are suitably used as magneto-optical devices, particularly as Faraday rotators of optical isolators with wavelengths of 0.9 to 1.1 μm.

[0061] FIG. 1 is a cross-sectional view showing an example of an optical isolator, which is a magneto-optical device including a Faraday rotator made of the paramagnetic garnet-type transparent ceramics according to the present embodiment as an optical element. As shown in FIG. 1, the optical isolator 100 includes a Faraday rotator 110 made of the above-mentioned paramagnetic garnet-type transparent ceramics, a polarizer 120 made of a polarizing material, and an analyzer 130 inside the housing 150. These are arranged in the order of the polarizer 120, the Faraday rotator 110, and the analyzer 130 along the optical axis 104 of the Faraday rotator. The polarized light vibration plane of the polarizer 120 and the polarized light vibration plane of the analyzer 130 are arranged so that the relative angle is 45°. In addition, the optical isolator 100 includes a magnet 140 for applying a magnetic field to the Faraday rotator 110 on at least one of the side surfaces of the Faraday rotator 110 inside the housing 150.

[0062] Such an optical isolator 100 can be suitably used in an industrial fiber laser device (not shown). The optical isolator can prevent the reflected light of the laser light emitted from the laser light source from returning to the light source, causing the oscillation to become unstable. EXAMPLES

[0063] EXAMPLES The present invention will be described in more detail below with reference to examples, comparative examples and reference examples, but the present invention is not limited to these examples.

[0064] [Example 1, Comparative Example 1, Reference Example 1] Example 1 shows a case where x, y, and z in formula (1) are 0.10≦x<1.35, 0.05≦y<0.30, and 4.80≦z≦4.98. Comparative Example 1 shows a case where y=0 and z=5.00 in formula (1). Reference Example 1 shows a case where x=1.35 or y=0.30 in formula (1).

[0065] Terbium oxide powder, yttrium oxide powder, and lutetium oxide powder manufactured by Shin-Etsu Chemical Co., Ltd., and aluminum oxide powder manufactured by Taimei Chemical Co., Ltd. were obtained. In addition, tetraethyl orthosilicate (TEOS) manufactured by Kishida Chemical Co., Ltd. and polyethylene glycol 200 liquid manufactured by Kanto Chemical Co., Ltd. were obtained. The purity of the powder raw materials was 99.9% by mass or more, and the purity of the liquid raw materials was 99.999% by mass or more. Using the above raw materials, the following oxide raw materials with a total of 12 types of chemical compositions were prepared by adjusting the mixing ratio to obtain the final composition shown in Table 1.

[0066] [Table 1]

[0067] Next, each was placed in a polyethylene pot, taking care to prevent mixing, and polyethylene glycol 200 was added as a dispersant to the oxide raw material at 0.5% by mass. Each was dispersed and mixed in ethanol using a ball mill. The processing time was 24 hours. After that, a spray drying process was carried out to produce granular raw materials with an average particle size of 20 μm.

[0068] The granular raw materials were then subjected to uniaxial pressing and isostatic pressing at a pressure of 198 MPa to obtain CIP compacts, which were then degreased in a muffle furnace at 1,000°C for 2 hours.

[0069] This degreased body was placed in a vacuum heating furnace and pre-sintered at 1,600°C for 2 hours to obtain a pre-sintered body. At this time, the sintered relative density of each sample was 94% or more. Each pre-sintered body obtained was placed in a HIP furnace made of a carbon heater and subjected to pressure sintering (HIP) treatment in Ar under conditions of 196 MPa, 1,600°C, and 3 hours. Next, the HIP-treated pressure sintered body was placed again in the vacuum heating furnace and sintered to a density of 1.0 × 10 -3 The ceramics were then re-sintered at 1,700°C for 20 hours under reduced pressure of less than 1 Pa. Finally, the re-sintered bodies were subjected to oxidation annealing at 1,450°C for 30 hours under normal atmospheric pressure to obtain oxidation annealed bodies. After oxidation annealing, the ceramics were all colorless and transparent in appearance.

[0070] The thus obtained oxidized annealed body (Example) and pressure sintered body (Comparative Example) were each ground into a cylindrical shape with a diameter of 5 mm, and both end faces were optically polished with an optical surface precision of λ / 8 (when the measurement wavelength λ=633 nm) to a length (optical path length) of 20 mm.

[0071] For the optically polished samples for measuring the insertion loss, anti-reflection films designed to have a central wavelength of 1,064 nm and a reflectance of 0.1% or less were applied to both end faces. The following measurements were performed on each sample obtained in the above manner.

[0072] (Verde constant) The Verdet constant V was calculated based on the following formula: The magnitude (H) of the magnetic field applied to the sample was calculated by simulation from the dimensions of the measurement system, the residual magnetic flux density (Br), and the coercive force (Hc). θ=V×H×L (In the formula, θ is the Faraday rotation angle (min), V is the Verdet constant, H is the magnitude of the magnetic field (Oe), and L is the length of the Faraday rotator (2.0 cm in this case.) The Verdet constant min / (Oe cm) calculated above was converted to the International System of Units (rad / (T m).)

[0073] (insertion loss) The insertion loss was measured by the light intensity when light with an intensity of 20 mW and a wavelength of 1,064 nm was narrowed down to a beam diameter of 200 μmφ and transmitted through the optically effective area of ​​the sample using an in-house optical system made with a light source manufactured by NKT Photonics, a collimator lens, a work stage, a power meter manufactured by Gentec, and a Ge photodetector, and was measured in dB based on the following formula: Then, a mechanism was added to the work stage on which the sintered compact sample was placed, which allowed it to move up, down, left, and right with an auto stepping motor, and the above-mentioned insertion loss measurement was repeated while moving the sintered compact sample from end to end at 100 μm pitches, thereby measuring the insertion loss distribution over the entire optically effective diameter (area), and the average value was read as the insertion loss based on the central 2 mm square value of the optically effective area obtained at this time. Insertion loss (dB / 20mm) = -10 × log 10 (I / I0) (In the formula, I is the transmitted light intensity (the intensity of light transmitted in a straight line through a sample with a length of 20 mm), and I0 is the incident light intensity.)

[0074] (Beam diameter change rate due to thermal lens) The rate of change in beam diameter due to the thermal lens was measured using a collimated CW laser beam manufactured by IPG Co., Ltd. with a wavelength of 1,070 nm, an output power of 100 W, and a diameter of 1.6 mm. This laser beam was projected onto a Coherent ModeMaster PC M 2The beam diameter at the reference plane (full bezel) of the profiler was measured using a beam propagation analyzer. Because the output power was high, the intensity of the laser light was attenuated to 1 / 1000 or less by a beam separator before being introduced into the beam profiler. The distance between the reference plane (full bezel) of the beam profiler and the sample holder was 1.9 m, and the distance between the reference plane and the collimator was 2.1 m. First, the beam diameter of the original beam (incident light) was measured, and the value at this time was taken as r0. Next, each sample with a length of 20 mm was placed in the light path, and the beam diameter of each transmitted light was measured and taken as r. As the absolute value of the beam diameter change rate in the present invention, |(1-r / r0)|×100(%) was calculated.

[0075] The above results and the measured values ​​of a TGG single crystal (diameter 5 mm, length 20 mm) manufactured by Northrop Grumman as Reference Examples 1-3 are summarized in Table 2.

[0076] [Table 2]

[0077] From the above results, it was confirmed that the paramagnetic garnet-type transparent ceramics of Examples 1-1 to 1-9 and Reference Examples 1-1 to 1-2 have a Verdet constant at a wavelength of 1,064 nm of 30 rad / (T·m) or more, an insertion loss of light excluding reflection at a wavelength of 1,064 nm over an optical path length of 20 mm of 0.05 dB or less, and an absolute value of the rate of change in beam diameter due to thermal lensing when laser light with a wavelength of 1,070 nm and an optical path length of 20 mm is incident with a beam diameter of 1.6 mm and an incident power of 100 W is 15% or less. In contrast, the paramagnetic garnet-type transparent ceramic of Comparative Example 1-1, where y = 0 and z = 5 in formula (1), had a Verdet constant of 34 rad / (T·m) or more at a wavelength of 1,064 nm, an insertion loss of light excluding reflection at a wavelength of 1,064 nm with an optical path length of 20 mm of 0.12 dB or less, and an absolute value of the rate of change in beam diameter due to thermal lensing was 18% when laser light with a wavelength of 1,070 nm and an optical path length of 20 mm was incident with a beam diameter of 1.6 mm and an incident power of 100 W. In other words, it was confirmed that a transparent ceramic with small insertion loss of light and small rate of change in beam diameter due to thermal lensing could be obtained when 0.15≦x<1.35, 0.05≦y<0.30, 4.80≦z<5.00, and 5.00≦y+z in formula (1) were satisfied.

[0078] [Example 2] As an example of a magneto-optical device, Example 2 shows an example of an optical isolator constructed using paramagnetic garnet-type transparent ceramics (Examples 1-5). Both end faces of a cylindrical transparent ceramic were optically polished to a diameter of 4.0 mm and a length of 17.0 mm. Furthermore, both end faces were coated with an anti-reflection film designed to reduce the reflectance of light with a wavelength of 1,064 nm to 0.1% or less. An optical isolator with the same configuration as that of Patent Document 8 was fabricated using this transparent ceramic as a Faraday rotator.

[0079] (Optical isolator performance test) As performance tests of the optical isolator, insertion loss and isolation were measured with reference to JIS C5932-2:2019. Measurements were made using a CW laser light with a wavelength of 1,064 nm and an output power of 20 mW. The intensity P1 [W] of this laser light (20 mW in this case) was read with a power meter. Insertion loss was measured by reading the transmitted light intensity P2 [W] with a power meter when light was inserted in the forward direction of the optical isolator. Insertion loss (dB) was calculated using the following formula. Insertion loss (dB) = -10log 10 (P2 / P1)

[0080] Next, the isolation was measured by inserting light in the reverse direction into the optical isolator and reading the transmitted light intensity P3 [W] with a power meter. The isolation (dB) was calculated using the following formula. Isolation (dB) = -10log 10 (P3 / P1)

[0081] The optical isolator equipped with the paramagnetic garnet-type transparent ceramics having the characteristics of Example 1-5 had an insertion loss of 0.17 dB and an isolation of 47 dB. As described above, it was confirmed that the paramagnetic garnet-type transparent ceramics produced in this example functioned as a Faraday rotator for an optical isolator.

[0082] Although the present invention has been described above using the above-mentioned embodiments, the present invention is not limited to these embodiments, and can be modified within the scope of what a person skilled in the art can imagine, such as other embodiments, additions, modifications, deletions, etc., and any aspect is within the scope of the present invention as long as it achieves the effects of the present invention. [Explanation of symbols]

[0083] 100 Optical isolator 110 Faraday Rotator 104 Optical axis 120 Polarizer 130 Analyzer 140 Magnet 150 Case

Claims

1. A paramagnetic garnet-type transparent ceramic comprising a sintered body containing 99 mass percent or more of a composite oxide represented by the following formula (1): Tb 8-x-y-z Y x Lu y Al z O 12 () (In the formula, 0.10≦x<1.35, 0.05≦y<0.30, 4.80≦z<5.00, and 5.00≦y+z.) A paramagnetic garnet-type transparent ceramic having an insertion loss of 0.05 dB or less for light at a wavelength of 1,064 nm, excluding reflection, over an optical path length of 20 mm.

2. SiO as a sintering aid 2 2. The paramagnetic garnet-type transparent ceramic according to claim 1, containing more than 0.00 mass % and 0.10 mass % or less of

3. 3. The paramagnetic garnet-type transparent ceramic according to claim 1, which has a Verdet constant of 30 rad / (T·m) or more at a wavelength of 1,064 nm.

4. 3. The paramagnetic garnet-type transparent ceramic according to claim 1 or 2, wherein the absolute value of the rate of change in beam diameter due to thermal lensing is 15% or less when laser light having a wavelength of 1,070 nm and an optical path length of 20 mm is incident with a beam diameter of 1.6 mm and an incident power of 100 W.

5. 3. A magneto-optical device comprising the paramagnetic garnet-type transparent ceramic according to claim 1.

6. 6. The magneto-optical device according to claim 5, which is an optical isolator having the paramagnetic garnet-type transparent ceramic as a Faraday rotator and having polarizing materials in front of and behind the optical axis of the Faraday rotator and usable in the wavelength range of 0.9 μm or more and 1.1 μm or less.

Citation Information

Patent Citations

  • Paramagnetic garnet transparent ceramic, magnetic optical material and magnetic optical device

    JP2019199386A

  • Paramagnetic garnet transparent ceramic, magnetic optical material and magnetic optical device

    JP2019199387A

  • Paramagnetic garnet-type transparent ceramic, magneto-optical device, and production method for paramagnetic garnet-type transparent ceramic

    WO2022054596A1

  • Tb-CONTAINING RARE EARTH-ALUMINUM GARNET CERAMIC, AND METHOD FOR MANUFACTURING SAME

    WO2022085679A1

  • Terbium-aluminum-garnet single crystal and method of manufacturing for the same

    JP2002293693A